Urban air quality in Europe - Viana, Mar (The Handbook of Environmental Chemistry, 2013)
This book provides an overview of air quality in urban environments in Europe, focusing on air pollutant emission sources and formation mechanisms, measurement and modeling strategies, and future perspectives. The emission sources described are biomass burning, vehicular traffic, industry and agriculture, but also African dust and long-range transport of pollutants across the European regions. The impact of these emission sources and processes on atmospheric particulate matter, ozone, nitrogen oxides and volatile and semi-volatile organic compounds is discussed and critical areas for particulate matter and nitrogen dioxide in Europe are identified. Finally, this volume presents future perspectives, mainly regarding upcoming air quality monitoring strategies, metrics of interest, such as submicron and nanoparticles, and indoor and outdoor exposure scenarios.